(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The primary school years are known to be the best for learning a foreign language. Imitation abilities, natural curiosity, and a desire for new knowledge all help to overcome the challenges of foreign language learning. A teacher who uses a foreign language introduces younger students to a different culture on the one hand, and fosters respect and tolerance for different lifestyles on the other.